(untitled) (Analysis in Theory and Applications, 2018)
In this article we introduce the paranormed sequence spaces ( f ,Λ, Δ_m, p), c_0( f ,Λ, Δ_m, p) and l_∞( f ,Λ, Δ_m, p), associated with the multiplier sequence Λ = (λ_k), defined by a modulus function f. We study their different properties like solidness, symmetricity, completeness etc. and prove some inclusion results.